(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluation of the ability to cover soft tissue defects in the upper leg area with the gastrocnemius muscle flap. Subject and method: A prospective case series was conducted on 19 patients with soft tissue defects in the proximal third of the leg (with exposed tendon, bone, or internal fixation) who underwent reconstruction using a pedicled gastrocnemius muscle flap. These cases were treated at the Department of Microsurgery and Reconstruction, Hospital for Traumatology and Orthopaedics Ho Chi Minh city from January 2020 to December 2024. All patients were followed for at least 2 months postoperatively to evaluate flap viability and outcome. Results: Complete flap survival was achieved in 18 of 19 cases (94.7%). In 17 patients the medial head of the gastrocnemius was used, and in 2 patients the lateral head was used. There was one case (5.3%) of total flap necrosis. Notable complications included one case of donor-site hematoma (requiring surgical evacuation) and one case of marginal skin necrosis around the flap resulting in bone exposure (requiring an additional local flap for coverage). The soft tissue defect sizes ranged from 3 × 4 cm to 7 × 8 cm. The gastrocnemius flaps were able to cover defects at various locations: primarily the anterior proximal tibia (15 cases, 78.9%), some involving the knee region (3 cases, 15.8%), and one case at the junction between the upper and middle thirds of the lower leg (5.3%). Conclusion: The gastrocnemius muscle flap proved to be a reliable solution for covering soft tissue defects in the proximal leg region. This flap can be designed to cover sizable defects due to its ample bulk and pedicle length with robust blood supply, and the harvest technique is relatively straightforward. However, when using the gastrocnemius flap as an island flap with near 180° rotation, one must take care to avoid pedicle kinking or compression. Incorporating a skin paddle with the muscle flap can also help extend the flap’s reach and coverage area when necessary.